2021
DOI: 10.1186/s13195-021-00913-5
|View full text |Cite
|
Sign up to set email alerts
|

Age, vascular disease, and Alzheimer’s disease pathologies in amyloid negative elderly adults

Abstract: Background We recently reported that CSF phosphorylated tau (p-Tau181) relative to Aβ40 (CSF p-Tau/Aβ40 ratio) was less noisy and increased associations with Alzheimer’s disease (AD) biomarkers compared to CSF p-Tau181 alone. While elevations of CSF p-Tau/Aβ40 can occur in amyloid-β (Aβ) negative (Aβ-) individuals, the factors associated with these elevations and their role in neurodegeneration and cognitive decline are unknown. We aim to explore factors associated with elevated tau in CSF, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…For example, sex differences in the prevalence of vascular-related risk factors exist where males have more vascular risk factors and vascular events than females before the ages of 70-75, 35 which have been associated with levels of CSF p-tau and Aβ 42 . 36 , 37 , 38 Sleep disturbances and increased wakefulness have been associated with Aβ and tau accumulation, as well as tau phosphorylation. 39 , 40 Insomnia is almost 1.5 times more common in females than males 41 and has been reported to be increased in APOE ε4 carriers, 42 although no known study has examined any sex- APOE interactions in association with sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sex differences in the prevalence of vascular-related risk factors exist where males have more vascular risk factors and vascular events than females before the ages of 70-75, 35 which have been associated with levels of CSF p-tau and Aβ 42 . 36 , 37 , 38 Sleep disturbances and increased wakefulness have been associated with Aβ and tau accumulation, as well as tau phosphorylation. 39 , 40 Insomnia is almost 1.5 times more common in females than males 41 and has been reported to be increased in APOE ε4 carriers, 42 although no known study has examined any sex- APOE interactions in association with sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…However, Aβ40/42 ratio was found to be positively correlated with WMHV in the whole SIVD patients. Recent studies found that Aβ0 and Aβ2 levels in cerebrospinal fluid were associated with WMHV ( Osborn et al, 2018 ; Guo et al, 2021 ), suggesting that Aβ40 and Aβ42 levels may be associated with white matter damage in SIVD patients. At the same time, we also found that WMHV was negatively correlated with CBF in the whole brain and GM, overall cognition, information processing speed, and executive function, while Jann et al (2021) also found that WMHV was associated with whole-brain perfusion and executive function in cerebral small vessel disease patients, which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling methodology differences might underlie the discrepancies. While the local Aβ and tau interaction (Aβ × tau) within the same region was modeled in their study [22], we used a summary cortical SUVR of several areas [31] to represent cortical Aβ burden, and Aβ plaques and regional tau tangles were modeled separately to distinguish their respective contributions in the downstream tau accumulations. Therefore, our ndings suggest that tau propagations depend more on existing tau tangles than cortical Aβ plaques in late tau-affected ROIs of Temporal-metaROI when Aβ plaques and tau tangles are already widespread in neocortex and Temporal-metaROI.…”
Section: Discussionmentioning
confidence: 99%
“…FBP or FBB standardized uptake value ratios (SUVRs) were obtained by normalizing regional FBP or FBB uptake to that in the whole cerebellum reference region. One AD summary cortical SUVR was calculated as a volume-weighted SUVR of frontal, cingulate, parietal, and lateral temporal regions, and A+ was de ned as AD summary cortical SUVR of FBP ≥1.11 or FBB ≥1.08, and FBP and FBB SUVRs were converted to Centiloids as described previously [31].…”
Section: Pet Imaging Processingmentioning
confidence: 99%